Caracterização ecomorfológica da comunidade de peixes de duas microbacias do Alto Rio Paraná - Oliveira, Elisa Martins de (Universidade Federal de São Carlos, 2016)
This study examined the ecomorphological pattern ofichthyofauna in two watersheds located on the Upper Paraná River. It was analyzed the ecomorphological variations of species collected from the Beija-Flor stream and Beija-Flor reservoir located in Estação Ecológica de Jataí and Lapa stream located in Área de Proteção Ambiental Corumbataí/Botucatu/Tejubá, to verify interspecific morphological differentiation, the effects oftrophic guilds along the ecomorphological patterns and the effects of water velocity along the ecomorphological standards. Of individuals collected in Estação Ecológica de Jataí, it was selected two Characidium species, on which the ecomorphological variations related to possibility of inter specific morphological differentiation of species of the same genus were analyzed. Considering the common species between the Estação Ecológica de Jataí and the Lapa Stream were observed morphological variables in order to verify the intraspecific morphological differences. Finally these results were related to the meaningof the relation ship between form and function. The main morphological differences found in the individuals of this study were related to the speed of water and feeding habits of the species. The distribution of species in morphological space showed the relation between the ecomorphological attributes and the distribution of species over the water column, where it was possible to characterize the species as demersal, nectobenthicand nektonic species. The relation ship of fish morphology with the water velocity is fundamental. The feeding also contributes with smaller importance in the separation of species in ecomorphological space, but this contribution seems to be because of the presence of these food items is also influenced by the speed of the water. The function of the species in the environmentin which they liveis linked mainly to its trophicniche.
Keywords: Ictiofauna; Variações ecomorfológicas; Forma e função; Ecologia trófica; Diversificação morfológica; Ichthyofauna; Ecomorphological variations; Form and function; Trophic ecology; Morphological diversification; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS